Perspective on Defective Semiconductor Heterojunctions for CO2 Photoreduction - Guo, Changfa (Langmuir : the ACS journal of surfaces and colloids, 2022)
Photocatalytic CO2 reduction to value-added chemicals is a green solution to concurrently address CO2 emission and energy issues, and semiconductor heterojunctions hold great potential to achieve such conversion. However, the photocatalytic performance of the existing heterojunctions is limited by the low interfacial charge transfer efficiency and sluggish surface reaction kinetics. To overcome these obstacles, defect engineering has been applied to heterojunctions to boost CO2 photoreduction in the past 5 years. This perspective summaries the key roles and the related mechanism of various anion vacancies located at the surface, interface, and both surface and interface of heterojunctions in photocatalytic CO2 reduction. Challenges in constructing and characterizating defective heterojunctions as well as in promoting their CO2 photoreduction activity and hydrocarbon selectivity are then outlined. Finally, some solutions to the rational design of defective heterojunctions for efficient and stable CO2 photoreduction are also proposed